Diagnosis of Nontuberculous Mycobacteria Lung Disease - Cowman, Steven A.; Loebinger, Michael R. (Seminars in Respiratory and Critical Care Medicine, 2018)
The diagnosis of pulmonary nontuberculous mycobacteria (NTM) disease may be challenging, as their presence alone does not necessarily indicate disease and diagnosis requires the integration of clinical, radiological, and microbiological findings. The first step is to suspect NTM disease; however, clinical manifestations of NTM are nonspecific and it may not be possible to separate them from those caused by underlying respiratory disease. The radiological appearance generally falls into two patterns, fibrocavitary disease and nodular-bronchiectatic disease; consolidation, infiltrates, and solitary nodules are also described. The isolation of NTM from clinical samples is fundamental to the diagnosis and they may be cultured from sputum, bronchoalveolar lavage fluid, or tissue specimens. If sputum is used, more than one isolate is required for diagnosis due to the propensity of NTM to contaminate clinical samples. The correct identification of NTM is vital, as their clinical relevance varies widely between species, and treatment is dictated by the identity of the isolated organism. This review covers the clinical presentation of NTM disease, the interpretation of radiological findings, and issues surrounding the isolation and identification of mycobacteria.
Keywords: nontuberculous mycobacteria; diagnosis; microbiological findings